Analisis Rasch terhadap Instrumen General Selfefficacy Scale-12 Versi Bahasa Indonesia: Studi Komparasi Rating Scale Model (RSM) dan Partial Credit Model (PCM) - Putra, Muhammad Dwirifqi Kharisma; Retnawati, Heri (Pusat Asesmen dan Pembelajaran, 2020)
Self-efficacy is one of the most researched topics in education and psychology, which grounded within social cognitive theory. Various instruments are available that can be used to measure general self-efficacy. As a foundational instrument in the measurement of general self-efficacy, the study investigated the psychometric properties of the General Self-Efficacy Scale-12 (GSES-12). Although the instrument has been adapted into Bahasa, the contribution of the Rasch measurement model in validating this instrument has never done before. By utilizing various advantages of the Rasch model, the polytomous Rasch model (RSM and PCM) were used. The data used in this study are secondary data from previous research. The sample consisted of 303 students (132 male, 171 female) with an age range 18 - 22 years old (mean age = 19.56, SD = 1.20). The results of Rasch's analysis show that the psychometric characteristics of GSES-12 are adequate. The data fit to the Partial Credit Model compared to Rating Scale Model. All assumptions in applying the Rasch model are fulfilled, and also the item fit to the model. Implications and suggestions for future research are also discussed.